2019
DOI: 10.1002/lary.28422
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal Nerve Stimulation in Veterans with Obstructive Sleep Apnea

Abstract: ObjectivesThe hypoglossal nerve stimulator (HNS) is an effective treatment for obstructive sleep apnea (OSA) in a relatively healthy subset of the population. Our aim was to determine the efficacy of HNS in a veteran population with a high incidence of chronic disease and mental health disorders. Our secondary aim was to compare subjective outcomes and adherence between veterans with and without mental health disorders.MethodsWe included all patients who underwent HNS at our institution to date. Veterans were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a retrospective case series of 31 Veterans Affairs patients, of whom 61% did not meet the FDA's proposed criteria, Sher's criteria was met in 90%, with 72% achieving an AHI less than 5. 1893 In addition, patients with isolated retropalatal collapse achieve similar results from HNS when compared to patients with other airway collapse patterns. 1894 An analysis of the ADHERE registry found that patients 65 years and older are more likely to have greater AHI reductions and higher device usage.…”
Section: Ixd7b Efficacy Of Hnsmentioning
confidence: 92%
See 1 more Smart Citation
“…In a retrospective case series of 31 Veterans Affairs patients, of whom 61% did not meet the FDA's proposed criteria, Sher's criteria was met in 90%, with 72% achieving an AHI less than 5. 1893 In addition, patients with isolated retropalatal collapse achieve similar results from HNS when compared to patients with other airway collapse patterns. 1894 An analysis of the ADHERE registry found that patients 65 years and older are more likely to have greater AHI reductions and higher device usage.…”
Section: Ixd7b Efficacy Of Hnsmentioning
confidence: 92%
“…Investigation continues into eligibility criteria for HNS since the literature postulates that a wider variety of patients may benefit from HNS than were included in the STAR trial. In a retrospective case series of 31 Veterans Affairs patients, of whom 61% did not meet the FDA's proposed criteria, Sher's criteria was met in 90%, with 72% achieving an AHI less than 5 1893 . In addition, patients with isolated retropalatal collapse achieve similar results from HNS when compared to patients with other airway collapse patterns 1894 .…”
Section: Surgical Treatment For Osamentioning
confidence: 99%
“…It is a highly efficacious treatment modality for improving OSA, even in veterans with mental health comorbidities. [36][37][38][39] Moreover, the device is well tolerated, and a recent meta-analysis revealed a 50% reduction in apnea-hypopnea index (AHI) with usage 86% to 96% of nights at 5.4 to 7.5 hours per night. 37,38 Despite these successes, there is no literature assessing the impact of comorbid insomnia on HNS adherence.…”
mentioning
confidence: 99%
“…The hypoglossal nerve stimulator (HNS) was approved by the US Food and Drug Administration (FDA) in 2014 and causes genioglossus muscle contraction and tongue protrusion on inspiration to prevent upper airway obstruction. It is a highly efficacious treatment modality for improving OSA, even in veterans with mental health comorbidities 36–39 . Moreover, the device is well tolerated, and a recent meta‐analysis revealed a 50% reduction in apnea‐hypopnea index (AHI) with usage 86% to 96% of nights at 5.4 to 7.5 hours per night 37 , 38 …”
mentioning
confidence: 99%
“…I read with interest the recent study by Sarber and colleagues, 1 in which they demonstrated the effectiveness of hypoglossal nerve stimulation in veterans with obstructive sleep apnea. Although strongly limited by sample size, the authors found suggestive evidence of increased effectiveness among veterans with comorbid mental health conditions.…”
mentioning
confidence: 99%